EKSISTENSI ZHIHAR DALAM HUKUM ISLAM: ANALISIS PERSPEKTIF FIQH SYAFI'IYYAH - Ibnu Mukti (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
The main purpose of marriage is to create a household full of peace, tranquility, love, and affection. However, in living a household life, various problems and issues often arise, one of which is the case of a husband who performs zhihar on his wife. This action can have legal consequences that require clear explanations and rules. In this case, Islam is present as a solution to the problem of zhihar, which during the Jahiliyah era was used as a way to divorce a wife. This study aims to examine the existence of kafarah zhihar according to the perspective of Fiqh Syafi'iyyah. The approach used is literature research with a qualitative normative method. The results of the study show that in Fiqh Syafi'iyyah, zhihar is a statement by a husband who equates his wife with a mother or with someone who is forbidden to marry, either because of blood relations, marriage, breastfeeding, or other reasons. Zhihar does not only occur by equating a wife with a mother, but also with other mahrams. There are two types of zhihar lafadz, namely clear ones (sharih) and figurative ones (kinayah), both of which require intention for the zhihar to be valid.